Case study of Philips / Muhammad Danish Ghazi Mohd Fakrurazi - Mohd Fakrurazi, Muhammad Danish Ghazi (2022)
The goal of this assignment is to identify the problem of a product. The company that I have chosen is Philips. From their vast selection of products, I have chosen the ADR620 dashcam for the analysis. In this case study, I have done the SWOT analysis to identify the strengths, weaknesses, opportunities, and threats of the ADR620. The primary issue that I have discovered with this ADR620 is that it has difficulties in navigating the application interface, unlike other Philips’ products such as their television, coffee machine, rice cooker, and many more. Based on the problem, the best solution that has been proposed is adding a touch screen feature to the ADR620 dashcam.